Pengaruh Kepemimpinan Stratejik Terhadap Strategi Bersaing UKM Café dan Restoran - Intan Widya Anugrah; Tintin Suhaeni (Jurnal Riset Bisnis dan Investasi, 2017)
Along with high competition, the ability to survive in the business world strategic leadership is needed to face the competition. Strategic leadership that has dimensions of vision, business model articulation, information delivery well, clever in handling power, and emotional intelligence is one of the factors needed in the company in choosing the appropriate strategy competitiveness. While the competitive strategy itself has a dimension of leadership that low cost, differentiation, and focus. This study aims to measure great strategic leadership, competitive strategy and how much strategic leadership relationship and competitive strategy in SMEs cafe and restaurant. The population of this study is 557 SMEs cafe and restaurant it Kecamatan Bandung Wetan, with a sample of 50 SMEs. The methodology used is descriptive method associative. In this study using simple regression method obtained regression equation Y = 16043 + 0,306X, it means to have a positive relationship of 0.401. The result of research stated that strategic leadership influence 16,08% toward competitive strategy at SMEs cafe and restaurant.